2009
DOI: 10.1186/1475-2891-8-17
|View full text |Cite
|
Sign up to set email alerts
|

Weight, physical activity and dietary behavior change in young mothers: short term results of the HeLP-her cluster randomized controlled trial

Abstract: Background: Preventing weight gain rather than treating established obesity is an important economic and public health response to the rapidly increasing rates of obesity worldwide. Treatment of established obesity is complex and costly requiring multiple resources. Preventing weight gain potentially requires fewer resources to reach broad population groups, yet there is little evidence for successful interventions to prevent weight gain in the community. Women with children are an important target group becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 29 publications
1
48
1
3
Order By: Relevance
“…Melhores níveis de atividade física relacionam-se com famílias de maior nível educacional, que entendem os benefícios, são mais ativas e atuam como apoio social, encorajando essa prática nos seus filhos 8,9,23 . A mãe com sobrepeso e fisicamente inativa pode afetar negativamente a decisão do adolescente sobre a prática de atividade física 9,30,31 . Apesar de a família influenciar a adoção de comportamentos saudáveis, deve-se observar que muitos adolescentes tendem a ignorar essas atitudes como forma de afirmar sua autonomia, tornando-se fisicamente inativos, independente do hábito da família 24 .…”
Section: Discussionunclassified
“…Melhores níveis de atividade física relacionam-se com famílias de maior nível educacional, que entendem os benefícios, são mais ativas e atuam como apoio social, encorajando essa prática nos seus filhos 8,9,23 . A mãe com sobrepeso e fisicamente inativa pode afetar negativamente a decisão do adolescente sobre a prática de atividade física 9,30,31 . Apesar de a família influenciar a adoção de comportamentos saudáveis, deve-se observar que muitos adolescentes tendem a ignorar essas atitudes como forma de afirmar sua autonomia, tornando-se fisicamente inativos, independente do hábito da família 24 .…”
Section: Discussionunclassified
“…Two of the interventions reported a positive effect on dietary intake (e.g. replacing high fat foods with low fat alternatives such as fruits and vegetables) and physical activity level (PAL) 41,42 while the other intervention reported favorable trends in the reduction of excessive weight gain and PAL 43 in the short term (4-12 months). In a prospective cohort study, Inskip et al 17 reported that out of 238 women who became pregnant during the first three months of the study period, those who intended a pregnancy were to some extent more inclined to follow recommendations as compared to those not planning a pregnancy.…”
Section: Multiple Health Behavior Interventionsmentioning
confidence: 99%
“…En este sentido, son muchos los estudios que informan de posibles mejoras en la salud de estas gestantes a través de la práctica regular de ejercicio físico moderado durante el embarazo [3][4][5][6][7][8][9][10] .…”
Section: Introductionunclassified